Algebraic Solution
- Half the perimeter of a rectangular room is 46 m, and its length is 6 m more than its breadth. What is the length and breadth of the room?
- 2m, 20m
- 2m, 3m
- 56m, 40m
- 26m, 20m
- Half the perimeter of a rectangular room is 46 m, and its length is 6 m more than its breadth. What is the length and breadth of the room?
Answer: (D) 26m, 20m
Solution: Let l and b be the length and breadth of the room. Then, the perimeter of the room = 2(l+b) metres
From question, l=6+b… (1)
×2(l+b) =46⟹l+b=46… (2)
Using the Substitution method:
Substituting the value of l from (1) in (2), we get
6+b+b = 46
⇒ 6+2b=46⟹2b = 40
⟹b =20 m.
Thus, l = 26 m
- Solve the following pair of equations: 2x+y=73x+2y = 12. Choose the correct answer from the given options.
- (-3,2)
- (1,0)
- (3,2)
- (2,3)
- Solve the following pair of equations: 2x+y=73x+2y = 12. Choose the correct answer from the given options.
Answer: (D) (2, 3)
Solution: We have,
2x+y=7 … (1)
3x+2y=12… (2)
Multiply equation (1) by 2, and we get:
2(2x+y) =2(7)
⇒4x+2y=14… (3)
Subtracting (2) from (3), we get,
x=2
Substituting the value of x in (1), we get,
2(2) +y=7⟹y = 3
Thus, the solution for the given pair of linear equations is (2, 3).
- Solve
- Y = 51/19
- X = 51/19
- Y = 94/57
- X = 117/54
- Solve
Answer: (A) Y = 51/19
Solution: (3x/2) – (5y/3) =2
LCM of 2 and 3 is 6. Multiply by 6 on both sides
9x−10y=−12 ————- (1)
(X/2) + (y/2) = 13/6
LCM is 6, so multiply by 6 on both sides
3x+3y=13 ————–(2)
Multiply equation (2) by 3 to eliminate x, so we get,
9x+9y=39……………(3)
Subtract (3) from (1) we have
−19y=−51⇒y = 51/19
Substitute this in one of the equations, and we get
- Given: 3x–5y=4; 9x=2y+7
Solve the above equations by the elimination method and find the value of x.
- X = 9/13
- Y = 5/13
- X = (-5) / 13
- Y = 9/13
Answer: (A) X = 9/13
Solution: Given:
3x–5y=4……(1)
9x=2y+7
9x−2y=7…..(2)
Multiply equation (1) by 3
⇒9x–15y=12…….(3)
Subtracting (2) from (3), we get,
−13y=5
Y= – ( (-5) / 13)
Substituting the value of y in (2)
All about Lines
- Choose the pair of equations which satisfy the point (1,-1)
- 4x–y = 3, 4x+y = 3
- 4x+y = 3, 3x+2y = 1
- 2x+3y = 5, 2x+3y = −1
- 2x+y = 3, 2x–y = 1
- Choose the pair of equations which satisfy the point (1,-1)
Answer: (B) 4x+y = 3, 3x+2y = 1
Solution: For a pair of equations to satisfy a point, the point should be their unique solution of them.
Solve the pair equations 4x+y=3,3x+2y = 1
let 4x+y=3…..(1)
and 3x+2y=1 …..(2)
y=3−4x [ From (1)]
Substituting value if y in (2)
3x+2y = 1
3x+2(3−4x) = 1
3x+6−8x = 1
−5x=−5⇒x = 1
Substituting x = 1 in (1),
4(1)+y=3⇒y = −1
⇒ (1,-1) is the solution of pair of equations.
∴ The pair of equations which satisfy the point is (1,-1).
Note: We can also substitute the value (1,-1) in the given equations and check if it satisfies the pair of equations or not. In this case, it only satisfies the pair of equation 4x+y=3, 3x+2y=1, and hence (1, -1) is the unique solution of the equation.
- 54 is divided into two parts such that the sum of 10 times the first part and 22 times the second part is 780. What is the bigger part?
- 34
- 32
- 30
- 24
- 54 is divided into two parts such that the sum of 10 times the first part and 22 times the second part is 780. What is the bigger part?
Answer: (A) 34
Solution: Let the 2 parts of 54 be x and y
x+y = 54…. (i)
And 10x + 22y = 780 ——————– (ii)
Multiply (i) by 10, and we get
Substituting y = 20 in x + y = 54, we have x + 20 = 54; x = 34
Hence, x = 34 and y = 20.
- What are the values of a, b and c for the equation y = 0.5x+√7 when written in the standard form: ax+by+c=0?
- 0.5, 1, √7
- 0.5, 1, – √7
- 0.5, -1, √7
- -0.5, 1, √7
- What are the values of a, b and c for the equation y = 0.5x+√7 when written in the standard form: ax+by+c=0?
Answer: (C) 0.5, -1, √7
Solution: Y= 0.5X + √7
⇒0.5x−y+ √7= 0
The general form of an equation is ax+by+c = 0.
Here, on comparing, we get
a = 0.5, b = −1 and c = √7
- Which of the following pairs of linear equations has infinite solutions?
Answer: (D) x+2y = 7; 3x+6y = 21
Solution: If two equations are consistent and overlapping, they will have infinite solutions. Option A consists of two equations where the second equation can be reduced to an equation which is the same as the first equation.
x+2y=7…. (i)
3x+6y=21….. (ii)
Dividing equation (ii) by 3, we get
x+2y=7 which is the same as equation (i).
The equations coincide and will have an infinite solution.
Alternate Method:
Let the two equations be
Basics Revisited
- Which of the following points lie on the line 7x+8y=61?
- (3, 4)
- (2, 5)
- (-3, 7)
- (3, 5)
- Which of the following points lie on the line 7x+8y=61?
Answer: (D) (3, 5)
Solution: Substituting the value of x = 3 and y = 4,
7x+8y = 61 = 7(3) +8(4) = 53.
Substituting the value of x = 2 and y = 5,
7x+8y=61 = 7(2) +8(5) = 54.
Substituting the value of x = -3 and y = 7,
7x+8y=61 = 7(−3) +8(7) =35.
Substituting the value of x = 3 and y = 5,
7x+8y=61 = 7(3) +8(5) =61
Hence, (3, 5) lies on the given line
- Which of these following equations have x = −3, y = 2 as solutions?
- 3x−2y = 0
- 3x+2y = 0
- 2x+3y = 0
- 2x−3y = 0
- Which of these following equations have x = −3, y = 2 as solutions?
Answer: (C) 2x+3y = 0
Solution: Substituting the values in LHS,
L.H.S = 2x+3y
L.H.S = 2(−3) +3(2)
L.H.S = 0 = R.H.S
Hence, x = −3, y = 2 is the solution of the equation 2x+3y = 0
- If y = 1/2 (3x+7) is rewritten in the form ax+by+c = 0, what are the values of a, b and c?
- ½, 7/2, 3/2
- 7, 2, 3
- -2, 3, -7
- -3, 2,-7
- If y = 1/2 (3x+7) is rewritten in the form ax+by+c = 0, what are the values of a, b and c?
Answer: (D) -3, 2,-7
Solution: The given equation is:
y = 1/2 (3x+7)
Simplifying the equation, we get the following:
2y−3x−7=0
⇒−3x+2y−7=0 (1)
Thus, the value of a, b and c is -3, 2 and -7, respectively.
The equation can also be written as,
3x−2y+7=0
Thus, the value of a, b and c is +3, -2 and +7, respectively.
Option D, -3, 2 and -7, is correct [Since +3, -2 and +7 is not an option]
- x−y=0 is a line:
- Passing through origin
- Passing through (1,-1)
- || to the y-axis
- || to the x-axis
- x−y=0 is a line:
Answer: (A) Passing through origin
Solution: x−y = 0, is a line passing through the origin as point (0, 0) satisfies the given equation
Graphical Solution
Statement 1: This is the condition for inconsistent equations
Statement 2: There exist infinitely many solutions
Statement 3: The equations satisfying the condition are parallel
Which of the above statements is true?
- S1 only
- S1 and S2
- S1 and S3
- S2 only
Answer: (C) S1 and S3
The condition is for inconsistent pair of equations which are parallel and have no solution.
∴ Statements 1 and 3 are correct.
Choose the correct statement.
- For k ≠ 3(m/5), a unique solution exists.
- For k = 3(m/5), infinitely many solutions exist
- For k = 5( m/3), a unique solution exists
- Fork = 5(m/3), infinitely many solutions exist
Answer: (D) For k = 5(m/3), infinitely many solutions exist
- The figure shows the graphical representation of a pair of linear equations. On the basis of the graph, the pair of linear equations gives ____________ solutions.
- Four
- Only one
- Infinite
- Zero
Answer: (B) Only one
Solution: If the graph of linear equations represented by the lines intersects at a point, this point gives the unique solution. Here, the lines meet at the point (1,-1), which is the unique solution of the given pair of linear equations.
- For what value of k do the pair of linear equations 3x+ky = 9 and 6x+4y = 18 have infinitely many solutions?
- -5
- 6
- 1
- 2
- For what value of k do the pair of linear equations 3x+ky = 9 and 6x+4y = 18 have infinitely many solutions?
Answer: (D) 2
Solution: Given equations gives infinitely many solutions if,
The given linear equations are:
3x+ky=9; 6x+4y=18.
⇒ 3/6 = k/4 = (-9)/ (-18)
⇒ ½ = k/4
⇒ k = 2
Solving Linear Equations
- Solve the following pairs of linear equation
- 9, 8
- 4, 9
- 3, 2
- ½, 1/3
Answer: (B) 4, 9
Solution: The pair of equations is not linear. We will substitute 1/x as u2 and 1/y as v2 then we will get the equation as
2u+3v=2
4u−9v=−1
We will use the method of elimination to solve the equation.
Multiply the first equation by 3, and we get
6u+9v=6
4u−9v=−1
Adding the above two equations
10u=5
u= ½
Substituting u in equation 4u−9v=−1 we get v= 1/3
- Solve the following pairs of the equation
(7x-2y) / xy=5
(8x+6y) /xy =15
- None of these
- 2, not defined
- 5/2, not defined
- (-2) /5, not defined
Answer: (A) None of these
Solution:
- x = -2, y = 2
- x = 7, y = -8
- x = 0, y = 8
- x = -1/5, y = 19/7
Answer: (D) x = -1/5, y = 19/7
- Solve the following pairs of equations:
(1/x) + (3/y) =1
(6/x)- 12/y = 2
- x = 5/3 , y = 15/2
- x = 4, y = 9
- x = 3, y = 11
- x = ¾ , y = 7/3
Answer: (A) x = 5/3, y = 15/2
Solution: Let 1/x = a and 1/y = b
(As x ≠ 0, y ≠ 0)
Then, the given equations become
a+3b = 1 … (1)
6a−12b = 2 … (2)
Multiplying equation (1) by 4, we get 4a+12b = 4 … (3)
On adding equation (2) and equation (3), we get 10a = 6
⇒a = 3/5
Putting a = 3/5 in equation (1), we get
(3/5) + 3b =1
⇒b= 2/15
Hence, x = 5/3 and y = 15/2
0 Comments